2022
DOI: 10.29100/jipi.v7i3.3154
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Ajar E-Book Berbasis Sains Model Addie Di Taman Kanak-Kanak

Abstract: 3) , ABSTRAKPengetahuan tentang sains dapat membantu perkembangan kognitif anak dalam berbagai cara. Guru dapat membantu meningkatkan pengetahuan sains peserta didik dengan menggunakan e-book dengan cara tetap memelihara budaya membaca. Banyak generasi milenial telah meninggalkan budaya membaca buku demi menggunakan teknologi yang lebih baru. Salah satu solusi untuk mengatasi masalah ini adalah dengan menyediakan e-book kepada peserta didik di Taman Kanak-kanak. Penelitian ini dirancang untuk mengembangkan med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Based on the research data results using the ADDIE model, it is shown that the development of e-book learning media to introduce science to young children, which has been tested at the TK Lab.School IKIP PGRI Jember, is highly suitable for implementation in early childhood science education. This aligns with what Ningrum and her colleagues expressed in their research on the development of the ADDIE model e-book media, which was conducted with the aim of providing a solution for introducing science in the children's surrounding environment (Ningrum et al, 2022).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Based on the research data results using the ADDIE model, it is shown that the development of e-book learning media to introduce science to young children, which has been tested at the TK Lab.School IKIP PGRI Jember, is highly suitable for implementation in early childhood science education. This aligns with what Ningrum and her colleagues expressed in their research on the development of the ADDIE model e-book media, which was conducted with the aim of providing a solution for introducing science in the children's surrounding environment (Ningrum et al, 2022).…”
Section: Discussionsupporting
confidence: 72%
“…Research on the development of e-book media has been conducted extensively (Ningrum et al, 2022) (Susilawati, 2022) (Novitasari et al, 2019) (Wulandari et al, 2019) (Kusumatuty et al, 2018) (Sanuaka et al, 2017), The results of research on the development of e-book learning media consistently show that this learning media is suitable and effective for use in education, and it can enhance the learning outcomes of students.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian ini merupakan penelitian pengembangan dengan model penelitian ADDIE. Model ADDIE dianggap lebih mudah untuk digunakan sebagai pedoman atau dasar dalam proses pengembangan produk pemebelajaran, karena tujuan model ADDIE untuk pendekatan produk dengan pengembangan yang intuitif dan efesien (Ningrum et al, 2022).…”
Section: Diskusiunclassified
“…Pemilihan model ADDIE dikarenakan tahapan proses pengembangan yang lebih sistematis dan jelas. Model ADDIE dianggap lebih mudah untuk digunakan sebagai pedoman atau dasar dalam proses pengembangan produk pembelajaran, karena tujuan model ADDIE untuk pendekatan produk dengan pengembangan yang intuitif dan efisien (Ningrum et al, 2022).…”
Section: Metode Penelitianunclassified